2012
DOI: 10.1029/2012jd017521
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of surface flux simulations to hydrologic parameters based on an uncertainty quantification framework applied to the Community Land Model

Abstract: [1] Uncertainties in hydrologic parameters could have significant impacts on the simulated water and energy fluxes and land surface states, which will in turn affect atmospheric processes and the carbon cycle. Quantifying such uncertainties is an important step toward better understanding and quantification of uncertainty of integrated earth system models. In this paper, we introduce an uncertainty quantification (UQ) framework to analyze sensitivity of simulated surface fluxes to selected hydrologic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
195
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(206 citation statements)
references
References 102 publications
(106 reference statements)
9
195
2
Order By: Relevance
“…Other modeling approaches often need additional data and longer time series to calibrate the model [Melsen et al, 2014]. Predictions of low flow conditions are often based on multimodel assessments [e.g., Prudhomme et al, 2014] that have large uncertainty in parameters related to subsurface runoff generation [Hou et al, 2012;Huang et al, 2013] and do not provide efficient guidance in understanding regional landscape differences.…”
Section: Discussionmentioning
confidence: 99%
“…Other modeling approaches often need additional data and longer time series to calibrate the model [Melsen et al, 2014]. Predictions of low flow conditions are often based on multimodel assessments [e.g., Prudhomme et al, 2014] that have large uncertainty in parameters related to subsurface runoff generation [Hou et al, 2012;Huang et al, 2013] and do not provide efficient guidance in understanding regional landscape differences.…”
Section: Discussionmentioning
confidence: 99%
“…The third is the appropriateness of the model parameter specification. How to estimate model parameters has received increasing attention from the hydrology and land surface modeling community over recent years (Franks and Beven, 1997;Gupta et al, 1999;Duan et al, 2001Duan et al, , 2003Jackson et al, 2003;Liu et al, 2005;Hou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The relative efficiency and effectiveness of several SA methods have been analyzed and compared. Hou et al (2012) introduced an uncertainty quantification framework to analyze the sensitivity of 10 hydrologic parameters in CLM4SP (Community Land Model Version 4 with satellite phenology) with a generalized linear model (GLM) method. They found that the simulation of sensible heat and latent heat is sensitive to subsurface runoff generation parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Other similar satisfactory optimization results were determined [54] by his research on hydrological parameter classifi cation. [54] has modeled in his studies on study [55][56][57][58], showing that the values of parameters on PCA diagrams can be presented as tables correlating between investigated parameters. At the same time, in order to identify the missing data and their uncertainties in complex computational models, a reliable approach to analysis is needed.…”
Section: Resultsmentioning
confidence: 99%